Analisis Faktor yang Mempengaruhi Keputusan Petani Padi di Desa Sindang Sono Kecamatan Sindang Jaya dalam Penjualan Gabah Kepada Tengkulak - Gryseska, Adrian; Wibowo, Aris Supriyo; Astuti, Andjar; saleh, Khaerul; Sulaeni, Sulaeni (Jurnal Penyuluhan dan Pemberdayaan Masyarakat, 2024)
Middlemen are one of the marketing options, although there are pros and cons to the existence. This study tries to understand and analyze the factors that allegedly influence the decision of rice farmers to sell grain to middlemen in Sindang Sono Village. The analysis used is quantitative with quantitative descriptive method. Research began in September 2023 through observation, questionnaires, interviews, and documentation. Sample calculation by simple random sampling with Slovin (alpha = 10%) resulted in 70 samples. The results showed that 81.43% of rice farmers sold to middlemen with the majority characteristics showing age between 50-59 years, male gender, elementary school education and below, family income <Rp5.000.000, the number of family dependents 4 people, the source of capital comes from themselves, the area of land cultivated <1 hectare, farming experience <20 years, land ownership status is cultivated, production levels ranged from 1.000-1.999 kg/season, the selling price was Rp 7.000-Rp 7.999, the type of grain was dry milled grain, no relationship with middlemen, and farmers' occupation was their main job. The binary logistic regression analysis test results show that together the variables of age, land status, and selling price have a significant effect (0.000). While partially, the variables of age (0,056), land status (0,001), and selling price (0,032) are partially affect (alpha 10%) the decision of rice farmers to sell to middlemen. While other alleged variables do not significantly affect the decision of farmers to sell to middlemen.